Building on feminist achievements to enhance choice for women seeking treatment. (6th May 2018) - Neale, Joanne; Tompkins, Charlotte N. E.; Marshall, Alison D.; Treloar, Carla; Strang, John
Abstract : Commentary to:Do women with complex alcohol and other drug use histories want women-only residential treatment?